Pendampingan Pembelajaran Metode Tilawah bagi Santri di Pondok Pesantren Nurul Amanah - Pratama, Syahroni Wahyu; Kurniawan, M. Febriano Andika; Pujiati, Tri; Dzikrulloh, Dzikrulloh; Fajar, Fajar (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
Students in Islamic boarding schools are expected to have the ability to read the Qur'an with tartil and beautifully so that the reading that is sung is beautiful to hear. In addition, students in Islamic boarding schools are expected to apply the tilawah method so that the reading of the Qur'an that is read can be more beautiful to hear. However, there are still students who do not understand the technique of reading the Qur'an using the tilawah method. This community service activity aims to provide assistance to students at the Nurul Amanah Islamic Boarding School in reading the Qur'an properly and correctly. This community service activity was designed using an Asset Based Community-driven Development (ABCD) approach strategy. This community service activity is carried out in the form of assistance to students when reading the Qur'an in the Islamic boarding school environment. This community service activity is carried out through 3 stages, namely (1) the preparation stage; (2) the mentoring stage; and (3) the evaluation stage. All stages of the activity are carried out well. The results of this community activity show that the tilawah method is suitable for students in the Nurul Amanah Islamic boarding school environment as an effort to improve the ability to read the Qur'an. The final results of this mentoring activity show that the students have a good understanding and increased ability in reading the Qur'an using the tilawah method.